Determinants of and Disparities in Reproductive Health Service Use Among Adolescent and Young Adult Women in the United States, 2002–2008 - Hall, Kelli Stidham (American Public Health Association, 2012)
Objectives. We investigated determinants of and disparities in reproductive health service use among young women in the United States from 2002 to 2008. Methods. Using data on 4421 US women aged 15 to 24 years from the National Survey of Family Growth (2002, n = 2157; 2006–2008, n = 2264), we employed descriptive and univariate statistics and multivariate regression models to examine service use across women's sociodemographic and reproductive characteristics and to investigate potential disparate changes in service use over time. Results. More than half the sample (59%) had used services in the past year. In regression models, predictors of service use included age, education, birthplace, insurance, religious participation, mother's education, childhood family situation, age at menarche, sexual intercourse experience, recent number of partners, and previous gynecological diagnosis. Although service use decreased by 8% overall from 2002 to 2006–2008 (P < .001), the magnitude of decline was similar across demographic and socioeconomic groups. Conclusions. Inequalities in reproductive health service use exist among women in the United States, particularly among the youngest and socially disadvantaged women, which may translate to poor and disparate reproductive outcomes. Public health and policy strategies are needed to eliminate inequities in reproductive health service.